Controlling invertebrate pests in agriculture [ - Page, Jessica; Horne, Paul A. [ (Paul Anthony)] , 1956- (CSIRO Publishing, 2012)
Controlling Invertebrate Pests in Agriculture discusses the principles of pest management and relates this to historical methods as well as current and future directions. It describes current practice, the concept of agricultural ecosystems, the role of pesticides and cultural control options. A separate chapter covers biological control and the different ways in which this may be implemented. The book provides a detailed examination of the application of pesticides, the different types that are available and how they may be integrated into more holistic approaches